LFP Oscillations in the Mesencephalic Locomotor Region during Voluntary Locomotion - Noga, Brian R.; Sanchez, Francisco J.; Villamil, Luz M.; O’Toole, Christopher; Kasicki, Stefan; Olszewski, Maciej; Cabaj, Anna M.; Majczyński, Henryk; Sławińska, Urszula; Jordan, Larry M. (Frontiers in Neural Circuits, 2017)
Oscillatory rhythms in local field potentials (LFPs) are thought to coherently bind cooperating neuronal ensembles to produce behaviors, including locomotion. LFPs recorded from sites that trigger locomotion have been used as a basis for identification of appropriate targets for deep brain stimulation (DBS) to enhance locomotor recovery in patients with gait disorders. Theta band activity (6-12 Hz) is associated with locomotor activity in locomotion-inducing sites in the hypothalamus and in the hippocampus, but the LFPs that occur in the functionally defined Mesencephalic Locomotor Region (MLR) during locomotion have not been determined. Here we record the oscillatory activity during treadmill locomotion in MLR sites effective for inducing locomotion with electrical stimulation in rats. The results show the presence of oscillatory theta rhythms in the LFPs recorded from the most effective MLR stimulus sites (at threshold ≤ 60 µA). Theta activity increased at the onset of locomotion, and its power was correlated with the speed of locomotion. In animals with higher thresholds (> 60 µA), the correlation between locomotor speed and theta LFP oscillations was less robust. Changes in the gamma band (previously recorded in vitro in the pedunculopontine nucleus, thought to be a part of the MLR) were relatively small. Controlled locomotion was best achieved at 10 - 20 Hz frequencies of MLR stimulation. Our results indicate that theta and not delta or gamma band oscillation is a suitable biomarker for identifying the functional MLR sites.